2013
DOI: 10.4028/www.scientific.net/msf.740-742.373
|View full text |Cite
|
Sign up to set email alerts
|

Deep Levels in P-Type 4H-SiC Induced by Low-Energy Electron Irradiation

Abstract: We have characterized deep levels in as-grown and electron irradiated p-type 4H-SiC epitaxial layers by the current deep-level transient spectroscopy (I-DLTS) method. A part of the samples were irradiated with electrons in order to introduce defects. As a result, we found that electron irradiation to p-type 4H-SiC created complex defects including carbon vacancy or interstitial. Moreover, we found that observed deep levels are different between before and after annealing, and thus annealing may change structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(16 reference statements)
1
4
1
Order By: Relevance
“…On the other hand, in our samples, there are no other deep levels corresponding to the reported deep levels. [11][12][13][14][15][16][17][18][19] The deep levels in our samples are mostly observed below 200 K, while, in the previous reports, DLTS measurements were performed above 200 K. Thus, the deep levels in our samples were not observed in the previous reports. As discussed above, in particular for the samples without annealing, the deep levels observed in this study (AP1, as1, e16-1, e17-1, and e17A-1) may become recombination centers.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…On the other hand, in our samples, there are no other deep levels corresponding to the reported deep levels. [11][12][13][14][15][16][17][18][19] The deep levels in our samples are mostly observed below 200 K, while, in the previous reports, DLTS measurements were performed above 200 K. Thus, the deep levels in our samples were not observed in the previous reports. As discussed above, in particular for the samples without annealing, the deep levels observed in this study (AP1, as1, e16-1, e17-1, and e17A-1) may become recombination centers.…”
Section: Discussioncontrasting
confidence: 53%
“…Finally, we compare the observed deep levels with those in the previous reports for p-type 4H-SiC. [11][12][13][14][15][16][17][18][19] For as-grown p-type 4H-SiC epilayers, Danno et al reported four deep levels labeled D, HK0, HK2, and HK4, [11][12][13] and Kawahara et al reported that the D and HK4 centers are dominant. 17) In our as-grown sample (As-grown), none of these deep levels were observed.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Researchers reported the ionization energy of the Al shallow acceptor [3][4][5][6][7][8][9] in SiC and we have already reported that the type deep levels (E a ~ + 0.32 eV) were newly discovered in Al + -implanted SiC samples other than the shallow Al acceptor level (E a ~ + 0.19 eV) [10]. These are located at much deeper level than the N shallow donor in SiC (~Ec -0.077 eV) and the B shallow acceptor in Si (~ Ea + 0.045 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, knowledge of the Al shallow acceptor is very limited; the ionization energy is different depending on papers [1][2][3][4][5][6][7], and the capture cross-section has been reported in only two papers [5,6]. In addition, few papers [6,8] have investigated deep levels near the valence band edge (~ E V + 0.3 eV or shallower), which can harmfully affect dynamic performance of 4H-SiC devices. To overcome the lack of knowledge and understand influence of those levels to the dynamic characteristics of 4H-SiC devices, we investigated the shallow and deep levels in p-type SiC epilayers using thermal admittance spectroscopy (TAS).…”
Section: Introductionmentioning
confidence: 99%